Combining grounded theory and case study methods in IT outsourcing study - Arshad, Yusri; Ahlan, Abdul Rahman; Syed Ibrahim, Sharifah Norhafiza (UTMSPACE, 2013)
Most early studies in information technology or system (IT/IS) predominantly apply quantitative techniques. However, application of qualitative methods is increasing in IT/IS researches and become a new trend among the researchers in the past twenty years. Using case studies are the most common methods to explore the research subjects. Recently, grounded theory method is becoming popular among doctoral candidates in their theses and also by researchers in reputable journals. In this research, the authors applied Simon’s model to investigate IT outsourcing case studies using both grounded theory and case study researches approaches. The authors, then, describe and discuss on grounded theory and case study methods and how they can be combined in an IT/IS study. The accounts of IT outsourcing study in Malaysia public healthcare agencies are chosen as an example. The study shows that application of both methods adds to rigorous, novelty and reliable theory building approach. Grounded theory and case study research did provide synergies in IS research particularly in providing rigorous and reliable iterative data collection and analysis to generate themes and an emerging theory. Moreover, there is a synergistically combination between case study research and grounded theory, demonstrating that qualitative approach is vibrant and flexible. We recommend future doctoral candidates to apply these two qualitative methods hand in hand.